2020
DOI: 10.1039/d0fo01835j
|View full text |Cite
|
Sign up to set email alerts
|

Differences in oral processing behavior of consumers varying in age, gender and ethnicity lead to changes in bolus properties but only to small differences in dynamic texture perception of sausages

Abstract: Consumer characteristics such as age, gender and ethnicity influence food oral processing behavior. The aim of this study was to determine the effect of age, gender and ethnicity on consumption...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 48 publications
3
7
0
Order By: Relevance
“…While previous studies with specific chewing protocols demonstrated that eating speed had a strong effect on bolus properties, flavor release, and consequently on texture and flavor perception (Luckett & Seo, 2017; Tarrega et al., 2008), our study shows that large differences in habitual eating speed have limited effect on dynamic sensory perception, which is in line with previous studies that categorized consumers according to their natural consumption time (Aguayo‐Mendoza et al., 2020; de Lavergne et al., 2015). Even though habitual slow eaters showed a better discrimination ability than habitual fast eaters, it seems that eating speed explains interindividual variability in dynamic sensory perception of foods only to a limited extent.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…While previous studies with specific chewing protocols demonstrated that eating speed had a strong effect on bolus properties, flavor release, and consequently on texture and flavor perception (Luckett & Seo, 2017; Tarrega et al., 2008), our study shows that large differences in habitual eating speed have limited effect on dynamic sensory perception, which is in line with previous studies that categorized consumers according to their natural consumption time (Aguayo‐Mendoza et al., 2020; de Lavergne et al., 2015). Even though habitual slow eaters showed a better discrimination ability than habitual fast eaters, it seems that eating speed explains interindividual variability in dynamic sensory perception of foods only to a limited extent.…”
Section: Resultssupporting
confidence: 92%
“…This is in general agreement with Aguayo‐Mendoza et al. (2020) who showed that dynamic texture perception of sausages was similar for consumers differing in age, gender, and ethnicity at the beginning and end of mastication and only minor differences in dynamic texture perception between consumer groups were observed during the middle stages of mastication with low dominance rates. We speculate that variations in habitual consumption time might cause considerable differences in bolus properties but do not necessarily lead to considerable difference in dynamic sensory perception.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Sensory analysis. A strict protocol was followed for the sensory assessment of the samples of sets 1 & 2 by an experienced, highly trained test panel of 11-14 members (experienced in evaluating products, not intentionally all female, average age 54.6 ± 7.4 years old; the panel's gender balance has previously been shown not to influence overall texture perception 56 ). Products were offered in a sequential monadic blind test using 3-digit codes.…”
Section: Methodsmentioning
confidence: 99%